Cellulose and cellulose derivatives in sustainable membrane development for oil/water separation - Chiam, Chel Ken; Zykamilia Kamin; Ng, Chi Huey; Farhana Abd Lahin; Rosalam Sarbatly (Arts and Science Press, 2024)
Cellulose is a natural polymer and most abundant organic substance on Earth. Inexhaustible hydroxyl groups on the cellulose surface allow derivatives of cellulose produced. This article discusses the recent progress of cellulose and cellulose derivatives in membrane development for oil/water separation. Functional groups that are available on the cellulose and its derivatives provide modification features to improve membrane wettability. Membranes with super wetting properties possess remarkable self-cleaning abilities which in turn can enhance permeation fluxes and extend membrane lifespan. However, the role of cellulose-based membranes in oily wastewater treatments is still in its early stages. This review article emphasizes on the development and modification of cellulose-based membranes for improvement of wettability, flux and separation efficiency, and the future directions of research.